THE EFFECT OF JOB SATISFACTION ON EMPLOYEE PERFORMANCE OF PT. SARASWANTI ANUGERAH MAKMUR MEDAN BRANCH - Pasaribu, Donald Frensius (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
This research aims to analyze the influence of job satisfaction on employee performance at PT. Saraswanti Anugerah Makmur Medan Branch. The research method used is quantitative, using survey techniques to distribute questionnaires to company employees. The research sample was taken randomly with a total of 143 employees, and the data was analyzed using simple linear regression to determine the relationship between job satisfaction variables and employee performance. The research results show that job satisfaction positively and significantly influences employee performance. The higher the job satisfaction employees feel, the better the resulting performance. These findings indicate that company management needs to pay attention to factors that influence job satisfaction, such as compensation, work environment, and career development, to increase employee productivity and loyalty. This research also provides implications for companies to focus more on policies that support balance between employees' work and personal lives to increase their satisfaction and performance. Suggestions for further research are to expand the variables studied and use the mixed method to gain a deeper understanding of other factors that influence employee performance.